2003
DOI: 10.1105/tpc.008623
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Dependence of Telomere Lengthening in ku80 Mutant Arabidopsis

Abstract: We have identified a ku80 mutant of Arabidopsis and show that telomerase is needed to generate the longer telomeres observed in this mutant. Telomeres are specialized nucleoprotein structures at the ends of chromosomes that permit cells to distinguish chromosome ends from double-strand breaks, thus preventing chromosome fusion events. Ku80 deficiency results in the lengthening of telomeres, a phenotype also seen in an Arabidopsis ku70 mutant. Furthermore, homogeneous populations of ku80 mutant cells show a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 66 publications
3
63
0
Order By: Relevance
“…Human RFC1 (RFC p140) can bind to the telomeric repeat and inhibit telomerase activity (Uchiumi et al, 1999). Mutations in DNA replication-related proteins, such as Pol a, RFC1, CTF18, and ELG1 in yeast, and KU70, KU80, and replication protein A 70a in Arabidopsis, increase telomere length (Gallego et al, 2003;Takashi et al, 2009). Here, we found that loss of function of ROS1 increased telomere length, while the impairing of RFC1 and other replication proteins decreased telomere length in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Human RFC1 (RFC p140) can bind to the telomeric repeat and inhibit telomerase activity (Uchiumi et al, 1999). Mutations in DNA replication-related proteins, such as Pol a, RFC1, CTF18, and ELG1 in yeast, and KU70, KU80, and replication protein A 70a in Arabidopsis, increase telomere length (Gallego et al, 2003;Takashi et al, 2009). Here, we found that loss of function of ROS1 increased telomere length, while the impairing of RFC1 and other replication proteins decreased telomere length in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited insight into the plant telomeres compared with mammalian systems, plant telomeres have recently attracted much interest, since it is becoming increasingly apparent that the function and architectural features of telomeres as well as the patterns of telomerase regulation are largely conserved in higher plants and animals (reviewed in Riha and Shippen, 2003a;McKnight and Shippen, 2004;Gallego and White, 2005;Lamb et al, 2007;Zellinger and Riha, 2007). As in human and other animal species, the stable maintenance of telomeres is essential for growth and development in Arabidopsis, and a number of nuclear proteins, such as RAD50, KU70/80, MRE11, Pot1/2, ATM, and ATR, have been shown to be involved in telomere regulation (Gallego and White, 2001;Riha and Shippen, 2003b;Gallego et al, 2003;Puizina et al, 2004;Shakirov et al, 2005;Vespa et al, 2005;Vannier et al, 2006). Disruption of the genes encoding these telomere-related proteins causes strikingly different developmental phenotypes accompanied by an abrupt onset of genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…A seedling growth assay on agar plates with bleomycin showed growth retardation of Arabidopsis At25 mutants comparable to Ku-null plants ( Figures 1D and 1E), indicating a deficiency in DNA repair. Inactivation of Ku in Arabidopsis leads to a 3-fold increase in telomere length and elevated telomeric recombination that results in the excision of extrachromosomal telomeric-circles (t-circles) (Riha et al, 2002;Gallego et al, 2003;Zellinger et al, 2007). While complementation of the KU80-null mutation with the wild-type KU80 prevented telomere elongation and t-circle formation, no suppression of these telomeric phenotypes was observed in plants complemented with the At25 construct ( Figures 1F and 1G).…”
Section: Ku Loading Onto Dna Is Required For Dna Repair and Telomere mentioning
confidence: 95%
“…Besides mediating protection of blunt-ended telomeres, Ku is also a negative regulator of telomerase in Arabidopsis (Bundock et al, 2002;Riha et al, 2002;Gallego et al, 2003;Riha and Shippen, 2003). It has been proposed that the dramatic elongation of Ku-depleted telomeres is caused by an increase in telomerase's access to unprotected chromosome termini (Kazda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation